1989
DOI: 10.1007/bf01258631
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in the rabbit retina and striatum: Diurnal rhythm and effect of light stimulation

Abstract: In rabbits, dopamine levels in the retina, but not in the caudate nucleus, showed clear diurnal rhythm, with high values seen in the light phase. Thirty min exposition of dark-adapted rabbits to day-light produced no changes in dopamine levels in the retina. In rabbits treated with alpha-methyl-p-tyrosine, the same light exposition decreased the retinal amine level by 18%, while stimulation with intensive, flickering light significantly decreased the retinal dopamine content by 36%. Experiments performed at no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…These changes were only observed when measured in the superfusate, but not when measured in tissues. Changes in endogenous DA levels induced by light have also been observed with strong stimulation, i.e., 30-min intensive flickering light (Nowak and Zurawska, 1989). Perhaps because of the different light condition used in the present work, we did not observe changes in DA at the tissue level.…”
Section: Discussionmentioning
confidence: 45%
“…These changes were only observed when measured in the superfusate, but not when measured in tissues. Changes in endogenous DA levels induced by light have also been observed with strong stimulation, i.e., 30-min intensive flickering light (Nowak and Zurawska, 1989). Perhaps because of the different light condition used in the present work, we did not observe changes in DA at the tissue level.…”
Section: Discussionmentioning
confidence: 45%
“…Daily rhythms in steady‐state levels of both dopamine and its major retinal metabolite, 3,4dihydroxyphenylacetic acid (DOPAC), with levels higher during the day than at night, have been reported in rat (Melamed et al . 1984; Gibson 1988; Pozdeyev and Lavrikova 2000), rabbit (Nowak and Zurawska 1989), human (Di Paolo et al . 1987) and fish (Kolbinger et al .…”
mentioning
confidence: 99%
“…It has been shown that melatonin in vitro inhibits dopamine release and in vivo decreases the retinal content of the catecholamine (Dubocovich 1983;Nowak and Żurawska 1989;Nowak et al 1992;Kazula et al 1993;Boatright et al 1994;Adachi et al 1998;Zawilska et al 2003a, b;Ribelayga et al 2004). In the current study, we demonstrated that injections of melatonin into the vitreous body during daytime significantly reduced, in a dose-dependent manner, the retinal levels of DOPAC.…”
Section: Discussionmentioning
confidence: 97%